The Risk Behavior of HIV/AIDS Transmission in The LGBT Group in Madiun - Ratnawati, Riska; Sulistiyaningrum, Ervina Maret (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Incidence of Human Immunodeficiency Virus (HIV)/ Acquired Immune Deficiency Syndrome (AIDS)  has been increasing for the last ten years in Indonesia, including Madiun, East Java. The purpose of this study was to determine factors influencing the risk of HIV/ AIDS transmission in lesbian, gay, bisexual and transgender (LGBT) group in Madiun, East Java. This was an analytical cross-sectional study, with study population being LGBT in Madiun, East Java. Sample of 64 LGBTs were selected by random sampling. The risk factors were age, sex, education, sexual behavior, sex workers status, income and knowledge. Data were collected by questionnaire and analyzed by multiple logistic regression. The risk of HIV infection decreased among LGBTs who were aged 17-25 years, had good knowledge and safe sexual behavior. The risk of HIV infection increased among LGBTs who were male,worked as sex worker and had low income. It can be concluded that the risk of HIV infection decreased among LGBTs,  who were aged 17-25 years, had good knowledge, and safe sexual behavior. The risk of HIV infection increased among LGBTs who were male,worked as sex worker, and had low income.